The experimental research on leaders and cooperative behavior - Fu, Xiaogai; Li, Chaoyang; Fu, Jialin (Frontiers in Psychology, 2022)
Leaders are critical to a team or organization. Because in addition to being at the core of decision-making, leaders' behavior also affects employees' psychology and work effort, thus affecting the efficiency and innovation of the team or organization. Previous studies have focused on the role model of leaders, ignoring the guiding role of leaders with different efforts. This paper introduces leader decision-making into the game of public goods to investigate the exemplary role of leaders in behavior decision-making. It divides them into three types by setting the investment amount of leaders to explore the mechanism of leaders' influence in behavior decision-making and behavior change of team members when facing the transformation of leaders with different investment types. This research can provide a significant reference value for enterprises and social organizations on how to play the role of leaders.